1995
DOI: 10.1080/00914039508031459
|View full text |Cite
|
Sign up to set email alerts
|

Ultra High Strength, High Modulus Polyethylene Spectra Fibers and Composites

Abstract: SPECTRA" polyethylene fibers are rapidly gaining acceptance in many applications in which high strength and modulus are required. They also represent a breakthrough in fiber technology because they represent the first case of a successful conversion of a flexible polymer into an ultra-strong fiber. Until the work of Pennings, who did the pioneering work on solution processing of ultra high molecular weight polyethylene, it was postulated that the manufacture of very strong extended chain fibers requires specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 19 publications
3
49
0
1
Order By: Relevance
“…At ballistic loading rates the fiber modulus values obtained were about half those obtained by Prevorsek et al [20] and Field and Sun [27], though were consistent with the high strain-rate values obtained by Lim et al [13]. Later on, Kavesh and Prevorsek [28] referred to an unpublished report wherein a Young's modulus of 230 GPa was calculated from a directly measured, tensile wave-speed in Spectra ® fiber, though the exact version and level of pre-tension was not specified.…”
Section: Experiments On Ballistically Measured Yarn Modulus and Strensupporting
confidence: 67%
“…At ballistic loading rates the fiber modulus values obtained were about half those obtained by Prevorsek et al [20] and Field and Sun [27], though were consistent with the high strain-rate values obtained by Lim et al [13]. Later on, Kavesh and Prevorsek [28] referred to an unpublished report wherein a Young's modulus of 230 GPa was calculated from a directly measured, tensile wave-speed in Spectra ® fiber, though the exact version and level of pre-tension was not specified.…”
Section: Experiments On Ballistically Measured Yarn Modulus and Strensupporting
confidence: 67%
“…Presumably, incorporation of uniformly dispersed and aligned CNTs in polymer matrix can provide polymer composites with dramatically improved strength and modulus in their machine direction. These expectations have recently been confirmed by a number of studies [26][27][28][29][30][31][32][33][34][35]. Our recent investigation [32][33][34] found that the achievable draw ratios (D ra ) of UHMWPE/carbon nanotubes (CNTs) asprepared fibers prepared near the optimal UHMWPE concentration improve consistently and reach a maximal value as their CNT and/or functionalized CNT contents increase up to an optimal value, respectively.…”
Section: Introductionsupporting
confidence: 56%
“…Several authors [16,[18][19][20][21][22] reported that the drawing temperature and rate could markedly affect the maximal achievable draw ratio and tensile properties of solution-grown UHMWPE samples. In addition to the gel solution compositions and drawing conditions, it is generally recognized that the conditions used in the formation process after spinning and/or solution casting of gel solutions can also have a significant influence on the morphology, microstructure and drawing properties of the specimens formed during the above mentioned processes [2,19,[23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Ultra high molecular weight polyethylene (UHMWPE) has been extensively used for various high performance application areas as biomedical, defence, etc [1,2]. However, its adverse properties such as creep, abrasion resistance, etc.…”
Section: Introductionmentioning
confidence: 99%